Risk factors for voice disorders in university professors in Cyprus - Kyriakou, Kyriaki; Petinou, Kakia; Phinikettos, Ioannis (My University, 2018)
Aims: The purpose of this study was to investigate risk factors for voice pathologies in university professors to determine the need for a preventative vocal hygiene education program that could improve the quality of life of university faculty. Methods: An online questionnaire was completed by 196 professors from 12 universities in Cyprus. The questionnaire elicited data regarding risk factors that may lead to voice disorders on parameters including general health, voice use, lifestyle, and environment and the self-perceived severity of a subject's voice problem. Subjects were divided into two groups based on their Voice Disorder Index (VDI) score: professors with VDI ≤5 and professors with VDI >5. The chi-square test was used to examine the differences in responses for each voice risk factor between the VDI ≤5 and the VDI >5 groups. Results: The VDI >5 group was more likely to frequently or sometimes experience respiratory infections, coughing, throat clearing, and stress, teach above students talking, and speak over their natural breath cycle than the VDI ≤5 group. Professors in the VDI >5 category were also more likely to have taught in very or moderately noisy environments than the VDI ≤5 group. Conclusions: Health, voice use, lifestyle, and environmental factors may contribute to the development of voice disorders in university professors in Cyprus. Therefore, a preventative vocal hygiene education program is recommended.
Keywords: Cyprus; Risk factors; University professors; Vocal hygiene; Voice disorders